2017
DOI: 10.3390/resources6010003
|View full text |Cite
|
Sign up to set email alerts
|

The Engagement of Students in Higher Education Institutions with the Concepts of Sustainability: A Case Study of the University of Northampton, in England

Abstract: Across higher education institutions there has, for some time, been a growing move towards incorporation of the concepts of sustainability into the policies and practices of the organisations. Using the University of Northampton, in the United Kingdom as a case study, this project aimed to understand the efficacy of student engagement with a sustainability project called Planet Too. The study employed a range of methods including waste and energy audits, as well as questionnaire surveys both with students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…In the previous research, it was found that environmental education, as a part of formal education, was able to help people to be aware and be concerned in relation to the environment, besides recognizing the consequences of their actions and having the ability to promote environmentally responsible behaviour among the students (Salequzzaman and Stocker, 2001). Besides that, according to Cleverdon et al (2017), there was a strong connection between what the students were practicing at home and their hostel. It was found that conserving water, conserving electricity, walking/cycling and recycling were among the key sustainability practices of students of the University of Northampton in England.…”
Section: Sustainable Development Concept Awareness Among Chemistry Learnersmentioning
confidence: 99%
“…In the previous research, it was found that environmental education, as a part of formal education, was able to help people to be aware and be concerned in relation to the environment, besides recognizing the consequences of their actions and having the ability to promote environmentally responsible behaviour among the students (Salequzzaman and Stocker, 2001). Besides that, according to Cleverdon et al (2017), there was a strong connection between what the students were practicing at home and their hostel. It was found that conserving water, conserving electricity, walking/cycling and recycling were among the key sustainability practices of students of the University of Northampton in England.…”
Section: Sustainable Development Concept Awareness Among Chemistry Learnersmentioning
confidence: 99%
“…Academics and education institutions [19,20] are seen as important elements of the circular economy. In light of this, the discussion on the sustainabilisation and ecologisation of fashion should naturally encompass fashion design education, in particular at the postsecondary level.…”
Section: The Need For Change In Fashion Design Educationmentioning
confidence: 99%
“…When such attitudes are embedded as an environmental identity, the positive effects on recycling are likely to be more pronounced (Watson et al , 2015). As a result, some argue that the focus should be targeted at increasing environmental identities rather than simply changing attitudes (Cleverdon et al , 2017; Freed, 2018). However, attitudes and motivations towards environmentally beneficial acts do not exist independently.…”
Section: Current Researchmentioning
confidence: 99%
“…It has been suggested that despite initiatives encouraging sustainability on university campuses, knowledge and awareness of sustainability is not increasing (Perrault and Clark, 2017b). In addition to this, the Student Sustainability Director of university accommodation provider, Unite, suggests that despite students having the most knowledge of environmental issues, they are the most environmentally reckless (Chaplin et al, 2014;Cleverdon et al, 2017;Cho, 2019;Kruger et al, 2020). However, concern for climate change within the student population is high at 91% (SUEZ, 2020) indicating the presence of a value action gap between concern for the environment but lack of action to act (Cho, 2019) due to the perceived inconvenience (SUEZ, 2020) and requirement of knowledge (Cho, 2019) There are several difficulties involved in researching recycling rates.…”
Section: Introductionmentioning
confidence: 99%